Rancang Bangun Alat Pengaduk Kue Secara Ergonomis Guna Meningkatkan Kapasitas Produksi di UMKM Airin - Muhammad Fadel Mahendra; Jaka Purnama (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
MSMEs in the home food industry often face limitations due to manual production equipment, which results in low productivity because operators or employees often experience pain when faced with prolonged dough mixing. This study aims to design an ergonomic cake mixer to improve production efficiency and productivity at Airin MSME. The literature review included concepts of work ergonomics, anthropometry with body measurements, and worker productivity. The research method used was a quantitative approach, collecting data through observation, interviews, and worker anthropometric measurements. Data were analyzed using uniformity tests and percentile calculations to determine appropriate tool dimensions. The results showed that the designed tool reduced production time, reduced operator workload, and improved dough quality consistency. Furthermore, the tool design complied with ergonomic principles based on user anthropometric data. In conclusion, the ergonomic cake mixer design has proven effective in increasing productivity and work comfort at MSMEs.